2022
DOI: 10.1002/mrm.29466
|View full text |Cite
|
Sign up to set email alerts
|

An interventional MRI guidewire combining profile and tip conspicuity for catheterization at 0.55T

Abstract: Purpose:We describe a clinical grade, "active", monopole antenna-based metallic guidewire that has a continuous shaft-to-tip image profile, a pre-shaped tip-curve, standard 0.89 mm (0.035 ′′ ) outer diameter, and a detachable connector for catheter exchange during cardiovascular catheterization at 0.55T. Methods: Electromagnetic simulations were performed to characterize the magnetic field around the antenna whip for continuous tip visibility. The active guidewire was manufactured using medical grade materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Design constraints related to RF-induced heating are eased at 0.55 T, allowing for increased flexibility in device configuration. A safe-by-design active guidewire with continuous shaft-to-tip profile that is mechanically comparable to off-the-shelf devices has been demonstrated for 0.55 T. 111 Additionally, a new technique of thin-film printed circuitry which can fabricate RF antenna components direction onto metallic surfaces with conductive ink has been demonstrated for needle devices at 0.55 T. 112 Most recently, interventional studies on a commercial 0.55 T system has demonstrated promising real-time imaging results despite the reduced gradient performance. Armstrong et al demonstrated cardiac catheterization, angioplasty, and stenting on the commercial 0.55 T (Fig.…”
Section: Mri-guided Invasive Proceduresmentioning
confidence: 97%
See 1 more Smart Citation
“…Design constraints related to RF-induced heating are eased at 0.55 T, allowing for increased flexibility in device configuration. A safe-by-design active guidewire with continuous shaft-to-tip profile that is mechanically comparable to off-the-shelf devices has been demonstrated for 0.55 T. 111 Additionally, a new technique of thin-film printed circuitry which can fabricate RF antenna components direction onto metallic surfaces with conductive ink has been demonstrated for needle devices at 0.55 T. 112 Most recently, interventional studies on a commercial 0.55 T system has demonstrated promising real-time imaging results despite the reduced gradient performance. Armstrong et al demonstrated cardiac catheterization, angioplasty, and stenting on the commercial 0.55 T (Fig.…”
Section: Mri-guided Invasive Proceduresmentioning
confidence: 97%
“…Design constraints related to RF‐induced heating are eased at 0.55 T, allowing for increased flexibility in device configuration. A safe‐by‐design active guidewire with continuous shaft‐to‐tip profile that is mechanically comparable to off‐the‐shelf devices has been demonstrated for 0.55 T 111 . Additionally, a new technique of thin‐film printed circuitry which can fabricate RF antenna components direction onto metallic surfaces with conductive ink has been demonstrated for needle devices at 0.55 T 112 …”
Section: Advanced Cardiac Mri Applicationsmentioning
confidence: 99%
“…Conspicuity is provided by the inclusion of iron oxide powder markers. An active guidewire, in commercial development in collaboration with NHLBI ( TRACR , Transmural Systems, Andover, Massachusetts), uses a modified loopless antennae to ensure conspicuity of the guidewire along its length [ 44 ] (see section on device visualization below).…”
Section: Guidewires For Icmrmentioning
confidence: 99%
“…Several types of device markers have been proposed to enhance the MRI visibility of interventional medical devices: passive, 21–24 active, 25–28 and semi‐active (resonant) markers 29,30 . Another approach generates local field disruption using tiny inductors, wherein a direct current (DC) is applied to the conductive wire wound around the device 31 .…”
Section: Introductionmentioning
confidence: 99%